"Islamic bank of Britain" case study analysis. (3rd November 2009) - Masood, Omar; Chichti, Jamel E.; Mansour, Walid; Iqbal, Muzafar
The Islamic banking system is expected to face strong competition not only from the Islamic banks but also from well-established conventional banks offering Islamic products and services. In this study, we focus on the 'Islamic Bank of Britain' the only indigenous bank of its kind in UK. The attempt is made to assess the degree of customer awareness, satisfaction as well as selection criteria. A sample of 200 respondents took part in this study. The responses where shows a certain degree of satisfaction, there few respondents also have expressed their dissatisfaction with some of the Islamic bank's services.